Profil Pemecahan Masalah dalam Pembelajaran Matematika dengan Model Problem Creating pada Siswa Kelas VII-2 SMP Negeri 1 Kota Bima - Sri Aryaningsih; Ramlan Mahmud; Nurdin Arsyad (Didaktik Matematika, 2016)
The purpose of this research are to examine: (i) the problem solving ability of class VII-2 students at SMPN 1 Bima City in mathematics learning process using problem creating model; (ii) the problem solving process of class VII-2 student at SMPN I Bima City in mathematics learning process using problem creating model. This research employed qualitative approach. Data was collected though observation of learning presentation and in-depth interview. The results of this research reveal that (i) the research subjects who have high, medium, and low ability are able to solve mathematics problems well by completing all the steps of mathematics problem. However, the research sebjects have less accuracy on each problem solving result without writing the conclusion of the answers; (ii) in general, class VII-2 students can solve the mathematics problems well, but the mistakes they do are no written conclusion on the answers obtained.